Central European Greylag Geese Anser anser show a shortening of migration distance and earlier spring arrival over 60 years. (2nd December 2016) - Podhrázský, Michal; Musil, Petr; Musilová, Zuzana; Zouhar, Jan; Adam, Matyáš; Závora, Jaroslav; Hudec, Karel
Abstract : Global climate change can cause pronounced changes in speciesʼ migratory behaviour. Numerous recent studies have demonstrated climate‐driven changes in migration distance and spring arrival date in waterbirds, but detailed studies based on long‐term records of individual recapture or re‐sighting events are scarce. Using re‐sighting data from 430 marked individuals spanning a 60‐year period (winters 1956/1957 to 2015/2016), we assessed patterns in migration distance and spring arrival date, wintering‐site fidelity and survival in the increasing central European breeding population of Greylag Geese Anser anser . We demonstrate a long‐term decrease in migration distance, changes in the wintering range caused by winter partial short‐stopping, and the earlier arrival of geese on their breeding grounds. Greylag Geese marked on central Europe moulting grounds have not been recorded wintering in Spain since 1986 or in Tunisia and Algeria since 2004. The migration distance and spring arrival of geese indicated an effect of temperature at the breeding site and values of the NAO index. Greylag Geese migrate shorter distances and arrive earlier in milder winters. We suggest that shifts in the migratory behaviour of Central European Greylag Geese are individual temperature‐dependent decisions to take advantage of wintering grounds becoming more favourable closer to their breeding grounds, allowing birds to acquire breeding territories earlier.